Exploring Java-China Fusion in Interior Design of Beauty Spa and Wellness Senopati - Zukhrufa, Azka; Pane, Sri Fariyanti; Mutiara, Maitri Widya (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The 2019 Savvy Sleeper study pinpoints Jakarta as a global center grappling with remarkably elevated stress levels, stemming from urban congestion, economic uncertainties, and socio-political challenges. A Regus survey underscores a substantial 64? Surge in stress levels in Indonesia, posing significant risks to both physical and mental health. In response, urban residents increasingly turn to healing activities, with spas emerging as vital contributors. Prasetyo et al.’s (2022) research emphasizes the favorable impact of spa experiences on stress reduction and overall well-being, stressing the need for thoughtfully designed spa facilities. The efficacy of spa experiences pivots on interior design, shaping ambiance and elevating relaxation. Recent studies underscore the importance of infusing elements of nature and cultural aesthetics into spa design to create a serene atmosphere. The fusion of Javanese and Chinese design elements, denoted as